A Look at the Nativization of Bangladeshi English through Corpus Data - Suárez-Gómez, Cristina; Seoane, Elena (Miscelánea: A Journal of English and American Studies, 2023)
This paper explores Bangladeshi English, a relative newcomer to the family of world Englishes. First, we chart the evolution of English in Bangladesh across several phases of development. These show that a number of political and ideological factors make the evolution of English in Bangladesh unique in that it wavers between the status of an exonormative foreign language (English in Bangladesh) and the development of a local variety (Bangladeshi English). From a linguistic perspective, recent studies agree that the current level of proficiency is very low, with a dearth of teachers and an absence of quality education. Second, we examine the degree of nativization of Present-day Bangladeshi English on the basis of (i) its postcolonial evolution and the more recent effects of globalization, following the most popular models of analysis (the Dynamic Model and the Extra- and Intra-Territorial Forces Model), and (ii) linguistic evidence obtained through the analysis of a selection of linguistic features associated with this variety, as represented in the GloWbE corpus.